Penerapan Metode Extreme Programming (XP) pada Pengembangan Sistem Informasi Penyewaan Lapangan Olahraga (SIPELA) - Kurniawan Kurniawan; Prabu Arta Mandala (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
The health was everyone's dream, so the sport is an alternative to be able to maintain physical fitness. Not everyone has the space and ability to have the sports equipment they want, so sports field rentals are an attractive business to do. The problem that occurs is that sports field rentals are not managed optimally, in addition to manual transactions it is also difficult to get information about empty field schedules, how much is the cost of field rental, how to find out the location and facilities provided by sports field tenants. The purpose of this research is to apply the extreme programming (XP) method to build a web-based meeting system between owners and tenants of sports fields to make it easier for users and managers of sports fields to interact directly with optimally. Based on the application of the XP method on the information system that was built, it really helped researchers in developing a system quickly and responsively to changes so that the system built, which was named SIPELA, could make it easier for sports field rental users to choose and determine which field rental suits their needs. admin staff can carry out administrative management activities quickly and easily and business owners can monitor and make decisions on all their business activities with better broad access.